Mechanisms of nitrogen and phosphorus release from heavily polluted coastal sediments and identification of influencing factor - Nana Hu; Yanqing Sheng; Qi Tang; Xiaozhu Liu (Environmental Research Communications)
The release of nitrogen (N) and phosphorus (P) from coastal sediments is vital to the evolution of coastal water quality. In this study, the release of N and P from coastal sediments in a heavily polluted river was studied using single-factor experiments and sequential extraction of N and P from sediments. The experimental results showed that N and P from the coastal river sediments reached the release-absorption equilibrium after the 42nd and 14th day, respectively. The release of N and P from heavily polluted river sediments in coastal zones is affected by resuspension, salinity, dissolved oxygen, and temperature. The results showed that resuspension had the greatest impact on the release of N and P from heavily contaminated coastal river sediments into the overlying water. In addition, the release of P, NO _3 ^− and NO _2 ^− from sediments is most sensitive to changes in temperature, while the release of total N and NH _4 ^+ is most sensitive to changes in salinity. Unlike in lake sediments, high dissolved oxygen concentrations inhibit the release of NH _4 ^+ from extensively contaminated coastal sediments. Ion-exchangeable forms of N and inorganic P are the most susceptible to release from external environmental factors. These findings will aid in the management and control of heavily polluted coastal rivers.